Liquidity Risk, Efficiency and New Bank Business Models - Carbó Valverde, Santiago; Cuadros Solas, Pedro Jesús; Rodríguez Fernández, Francisco (Palgrave Macmillan Studies in Banking and Financial Institutions, 2016)
This book provides insight into current research topics in finance and banking in the aftermath of the financial crisis. In this volume, authors present empirical research on liquidity risk discussed in the context of Basel III and its implications. Chapters also investigate topics such as bank efficiency and new bank business models from a business diversification perspective, the effects on financial exclusion and how liquidity mismatches are related with the bank business model. This book will be of value to those with an interest in how Basel III has had a tangible impact upon banking processes, particularly with regard to maintaining liquidity, and the latest research in financial business models.